Women, work, and the family in Europe - Drew, Eileen P.; Emerek, Ruth; Mahon, Evelyn (London ; New York : Routledge, 1998)
A new and timely analysis of major changes in society within the extended European Union. Addresses the consequences of altered family forms, the restructuring of the labour markets and the conflicting demands of family and working life.
Re-conceptualising families ; Changing family forms and the allocation of caring / Eileen Drew -- State policy and gender contracts : the Swedish experience / Yvonne Hirdman -- Greek family policy from a comparative perspective / Theodoros N. Papadopoulos -- Recent changes in family policy in France : political trade-offs and economic constraints / Jeanne Fagnani -- Paid work and care of older people : a UK perspective / Judith Phillips -- Employment and family lives : equalities and inequalities / Julia Brannen -- Employment, flexibility and gender / Eileen Drew and Ruth Emerek -- Part-time employment in a European perspective / Susan McRae -- Homeworking : new approaches to an old problem / Sheila Rowbotham and Jane Tate -- Labour policies, economic flexibility and women's work : the Italian experience / Daniela del Boca -- Atypical working time : examples from Denmark / Ruth Emerek -- Workplace culture, family-supportive policies and gender differences / Lis Højgaard -- Changing gender roles, state, work and family lives / Evelyn Mahon -- Modernisation of motherhood / Arnlung Leira -- Class, mothers and equal opportunities to work / Evelyn Mahon -- Working parents : experience from the Netherlands / Els Veenis -- Are fathers changing? : Comparing some different images on sharing of childcare and domestic work / Dino Giovannini -- Family orientation among men : a process of change in Sweden / Ulla Björnberg.
Includes bibliographical references (pages 208-222) and index.
Print version record.
English.
Keywords: Work and family -- Government policy -- Europe; Family policy -- Europe; Women -- Employment -- Europe; Travail et familles -- Politique gouvernementale -- Pays de l'Union européenne.; Politique familiale -- Pays de l'Union européenne.; Femmes -- Travail -- Pays de l'Union européenne.; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Family policy; Women -- Employment; Work and family -- Government policy; Europe; Electronic books; Electronic books